Yellow-green light-emitting single crystal material, preparation method thereof and yellow-green light-emitting device

The solution cooling and recrystallization method is used to prepare yellow-green luminescent single crystal materials at low temperatures, which solves the problems of scarce existing material resources and unstable luminescent performance, and achieves high-efficiency and low-energy consumption yellow-green luminescent effect, which is suitable for large-scale production.

CN119392370AActive Publication Date: 2025-02-07GANJIANG INNOVATION ACAD CHINESE ACAD OF SCI
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411509594.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-28
Publication Date
2025-02-07
Estimated Expiration
2044-10-28

AI Technical Summary

Technical Problem

Among the existing yellow-green luminescent materials, rare earth doped materials have scarce resources and high production costs. The photoluminescence efficiency of copper doped materials depends on the precise control of doping concentration and crystal structure, resulting in unstable luminescent performance.

Method used

The solution cooling and recrystallization method is used to prepare yellow-green luminescent single crystal material at a lower temperature. By uniformly doping luminescent centers in soluble alkali metal iodide crystals, a new luminescent center is formed, which improves luminescence consistency and quantum yield.

Benefits of technology

It has achieved a yellow-green luminescent material with uniform copper ions distribution, high luminescence efficiency, low energy consumption and high production efficiency. The luminescent quantum yield can reach 98.98%, which is suitable for large-scale production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119392370A_ABST
    Figure CN119392370A_ABST
Patent Text Reader

Abstract

The invention relates to a yellow-green light-emitting single crystal material, a preparation method thereof and a yellow-green light-emitting device. The preparation method comprises the following steps: mixing soluble alkali metal iodide with soluble luminescent central ion halide, and dissolving the mixture in an acid solution at a first dissolving temperature to obtain a reactant solution; cooling the reactant solution from the first dissolving temperature to a first crystallization ending temperature according to a first cooling rate to obtain first crystal grains; and placing the first crystal grains in the reactant solution at a second dissolution temperature, and cooling to a second crystallization ending temperature according to a second cooling rate to obtain the yellow-green light-emitting single crystal material. The quantum yield of the yellow-green light-emitting single crystal material in the yellow-green wave band can reach up to 98.98%, the preparation method is simple, and the production period is short.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of preparation and application of optoelectronic materials, and relates to a luminescent material, and in particular to a yellow-green luminescent single crystal material and a preparation method thereof, and a yellow-green luminescent device. Background Art

[0002] In the field of optics and optoelectronic materials, yellow-green luminescent materials have attracted much attention from researchers due to their wide applications in display technology, lighting devices, optical sensors, etc. Yellow-green light is located in the middle of the visible spectrum (about 560nm to 580nm), which is suitable for human eye perception, so it plays an important role in a variety of optical applications.

[0003] However, among the existing yellow-green luminescent materials, the most common are rare earth-doped inorganic salt materials, such as inorganic salt materials doped with rare earth elements such as europium (Eu), cerium (Ce), and terbium (Tb). Although such materials have high luminous efficiency, rare earth element resources are scarce and expensive, and the extraction and production processes cause great environmental pollution. In addition, the preparation of rare earth-doped inorganic salt materials usually involves complex high-temperature solid-phase reactions or other time-consuming high-temperature processes or crystal growth processes, and the preparation cost is high, which is difficult to meet the needs of large-scale industrial applications.

[0004] In recent years, copper (Cu), as a relatively cheap and abundant transition metal, has been widely studied for doping various optical materials. Copper-containing metal halides have become an important class of photoluminescent materials due to their low cost, low toxicity, abundant reserves and excellent optical properties. + or Cu 2+ ) can regulate the optical properties of materials through specific lattice doping to produce visible light emission. However, the photoluminescence efficiency of copper-doped materials usually depends on the precise control of doping concentration, crystal structure and crystal growth process. In the prior art, whether it is rare earth-doped or copper-doped materials, the distribution of doping elements in the crystal is often uneven, resulting in unstable luminescence performance and reducing the luminescence efficiency of the material. Therefore, it is necessary to optimize the synthesis method to ensure that copper ions are evenly distributed and effectively activate the luminescence performance.

[0005] CN112480911A discloses a method for preparing Cu-doped Cs2AgI3 perovskite, which includes transferring the ball-milled powders of cesium iodide and silver iodide to a hydrothermal reactor, adding cuprous iodide, hydroiodic acid, and hypophosphorous acid, and hydrothermally treating them at a temperature of 150°C to 200°C, and then cooling them at a temperature of -10°C to -35°C to obtain Cs2AgI3:Cu crystals with high purity and enhanced fluorescence efficiency. This method requires high-temperature hydrothermal reaction and low-temperature cooling treatment, which is cumbersome and complicated. However, the quantum yield of the obtained Cs2AgI3:Cu crystal can only reach 65.8%, and it can only emit blue light, and cannot emit yellow-green light.

[0006] CN116855750A discloses a method for preparing a Cs3Cu2I5:Mn single crystal scintillator with high light yield, ultrafast scintillation attenuation and low cost, comprising the steps of fully mixing and dispersing cuprous iodide, cesium iodide, manganese oxide, hydroiodic acid and hypophosphorous acid to obtain a mixed solution, keeping the mixed solution at a constant temperature of 64°C for 2 days, setting a cooling program to decrease the temperature by a constant rate of 0.1°C per day, and obtaining a seed crystal after cooling and growing for 15 days, fixing the seed crystal on a seed crystal rack, placing the seed crystal in the mixed solution, cooling the mixed solution at a rate of 0.1°C / day and a seed crystal rotation speed of 60 revolutions / min, and obtaining a Cs3Cu2I5:Mn single crystal scintillator with high light yield, ultrafast scintillation attenuation and low cost after cooling and growing for 30 days. Although the quantum yield of the obtained Cs3Cu2I5:Mn single crystal scintillator can reach 94.51%, it can only emit strong blue light but not yellow-green light. In addition, its preparation cycle exceeds one and a half months and its production efficiency is too low, which limits its feasibility and commercial development in large-scale applications.

[0007] Therefore, it is of great significance to provide a method for preparing a yellow-green luminescent material with uniform copper ion distribution, high luminescence efficiency, low energy consumption and high production efficiency. Summary of the invention

[0008] In view of the deficiencies in the prior art, the present invention provides a yellow-green luminescent single crystal material and a preparation method thereof and a yellow-green luminescent device. The present invention adopts a solution cooling recrystallization method, which is a low-energy consumption and easy-to-control crystal growth process, to achieve the preparation of a yellow-green luminescent single crystal material at a relatively low temperature. The solution cooling recrystallization method in the present invention can achieve uniform doping of luminescent center ions in soluble alkali metal iodide crystals at a relatively low temperature and promote the stable growth of soluble iodide crystals. The luminescent center ions can form new luminescent centers in the soluble alkali metal iodide lattice, giving it efficient luminescent characteristics in the yellow-green band, thereby improving the luminescent consistency and quantum yield of the yellow-green luminescent single crystal material. In addition, the temperature control of the solution cooling method is more precise and easy to operate, with high production efficiency, which is conducive to large-scale production.

[0009] To achieve this object, the present invention adopts the following technical solutions:

[0010] In a first aspect, the present invention provides a method for preparing a yellow-green luminescent single crystal material, the preparation method comprising:

[0011] (1) mixing a soluble alkali metal iodide and a soluble luminescent center ion halide to obtain a mixture;

[0012] (2) dissolving the mixture of step (1) in an acid solution at a first dissolution temperature to obtain a first reactant solution, and cooling the first reactant solution from the first dissolution temperature to a first end crystallization temperature at a first cooling rate to obtain first crystals;

[0013] (3) dissolving the mixture of step (1) in an acid solution at a second dissolution temperature to obtain a second reactant solution, adding the first crystal grains of step (2) to the second reactant solution, and cooling from the second dissolution temperature to a second end crystallization temperature at a second cooling rate to obtain the yellow-green light-emitting single crystal material;

[0014] The first reactant solution and the second reactant solution are both saturated solutions of soluble alkali metal iodides;

[0015] The acid solution includes a combination of hydroiodic acid and hypophosphorous acid.

[0016] It should be noted that the first grains in the present invention refer to the grains obtained after cooling to the first end crystallization temperature. "First" is only for the purpose of corresponding to the first dissolution temperature and the first end crystallization temperature. It has no other special meaning and does not have any limiting effect.

[0017] The present invention adopts the solution cooling recrystallization method, which is a low-energy consumption and easy-to-control crystal growth process, to achieve the preparation of yellow-green luminescent single crystal materials at a relatively low temperature, which meets the energy-saving and environmental protection requirements of modern industry.

[0018] The solution cooling recrystallization method of the present invention can realize uniform doping of luminescent center ions in soluble alkali metal iodide crystals at a relatively low temperature and promote the stable growth of soluble iodide crystals. The luminescent center ions can form new luminescent centers in the soluble alkali metal iodide crystal lattice, giving it efficient luminescent characteristics in the yellow-green band, thereby improving the luminescent consistency and quantum yield of the yellow-green luminescent single crystal material. In addition, the solution cooling method has more precise temperature control and is easy to operate, with high production efficiency, is suitable for large-scale production, and meets the market demand for efficient luminescent materials.

[0019] In step (2) and step (3), the first crystallization and the second crystallization are performed at the first cooling rate and the second cooling rate respectively. Since the first crystallization and the second crystallization are both performed in the reactant solution and the concentrations of the two crystallization solutions are consistent, controlling the cooling rate can effectively regulate the composition of the material precipitated in the solution, and then regulate the composition accumulated on the crystal surface, which is beneficial to the uniform distribution of the luminescent ion center in the material, ensuring the uniform distribution of the luminescent center ions in the soluble alkali metal iodide lattice, and the stable growth of the yellow-green luminescent single crystal material lattice.

[0020] After the first crystallization, the first crystal grains with good crystal quality are placed back into the reactant solution for second crystallization, which is beneficial for inducing ions to accumulate and crystallize on the surface of the first crystal grains and is beneficial for further growth of the crystal size.

[0021] Preferably, the first dissolution temperature in step (2) is 50-70°C, for example, it can be 50°C, 53°C, 55°C, 58°C, 60°C, 63°C, 65°C, 68°C or 70°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0022] The first dissolution temperature in the present invention is 50-70° C., in order to ensure that the soluble alkali metal iodide and the soluble luminescent center ion halide can be dissolved at the first dissolution temperature.

[0023] Preferably, the first end crystallization temperature in step (2) is 20°C-30°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0024] Preferably, the second dissolution temperature in step (3) is 50-70°C, for example, it can be 50°C, 53°C, 55°C, 58°C, 60°C, 63°C, 65°C, 68°C or 70°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0025] Preferably, the second end crystallization temperature in step (3) is 20°C-30°C, for example, it can be 20°C, 21°C, 22°C, 23°C, 24°C, 25°C, 26°C, 27°C, 28°C, 29°C or 30°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0026] Preferably, the first dissolution temperature is the same as the second dissolution temperature, and the first end crystallization temperature is the same as the second end crystallization temperature.

[0027] In the present invention, the first dissolution temperature is the same as the second dissolution temperature, and the first end crystallization temperature is the same as the second end crystallization temperature. On the one hand, the concentration of each reactant in the reactant solution and the crystal growth solution is guaranteed to be the same, which is conducive to the uniform dispersion of the luminescent center ions, thereby ensuring that the luminescent center ions are uniformly distributed in the soluble alkali metal iodide lattice, and on the other hand, the stable growth of the soluble alkali metal iodide lattice is guaranteed. Through the uniform distribution of the luminescent center ions in the soluble alkali metal iodide lattice and the stable growth of the soluble alkali metal iodide lattice, the luminescence consistency of the yellow-green luminescent single crystal material is jointly guaranteed, and the quantum yield of the yellow-green luminescent single crystal material in the yellow-green light band is improved.

[0028] Preferably, in step (2), the first cooling rate is 0.7°C / h-2°C / h, for example, it can be 0.7°C / h, 0.8°C / h, 0.9°C / h, 1°C / h, 1.1°C / h, 1.2°C / h, 1.3°C / h, 1.4°C / h, 1.5°C / h, 1.6°C / h, 1.7°C / h, 1.8°C / h, 1.9°C / h or 2°C / h, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 1°C / h-1.6°C / h.

[0029] Preferably, in step (3), the second cooling rate is 0.7°C / h-2°C / h, for example, it can be 0.7°C / h, 0.8°C / h, 0.9°C / h, 1°C / h, 1.1°C / h, 1.2°C / h, 1.3°C / h, 1.4°C / h, 1.5°C / h, 1.6°C / h, 1.7°C / h, 1.8°C / h, 1.9°C / h or 2°C / h, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 1°C / h-1.6°C / h.

[0030] Preferably, the first cooling rate is the same as the second cooling rate.

[0031] In the present invention, the first cooling rate and the second cooling rate are precisely controlled to ensure that the luminescent center ions are evenly distributed in the alkali metal iodide lattice during the crystallization process, the alkali metal iodide grows stably, the luminescent consistency and quantum dot yield of the yellow-green luminescent single crystal material are improved, and excellent luminescent performance is exhibited in the yellow-green spectral range.

[0032] The first cooling rate is the same as the second cooling rate. Since the concentrations of the two crystallization solutions are consistent, the composition of the material precipitated from the solution is consistent in the same time, and the composition accumulated on the crystal surface is almost consistent, which is conducive to the uniform distribution of the luminescent center ions in the crystal.

[0033] Preferably, the soluble luminescent central ion halide comprises copper iodide.

[0034] Preferably, the soluble alkali metal iodide comprises potassium iodide.

[0035] Potassium iodide is a common salt crystal with good optical transparency and physical and chemical stability, but it does not have luminescent properties. By doping potassium iodide crystals with luminescent central ions, new optical properties can be given to them, especially luminescent properties in the yellow-green spectrum. In addition, potassium iodide crystals are easy to grow through low-temperature techniques such as solution methods, which provides the possibility of developing low-cost and efficient luminescent materials.

[0036] The potassium iodide and copper iodide materials used in the present invention are both cheap and environmentally friendly compounds, which avoid the expensive cost of rare earth elements and their potential pollution to the environment and are suitable for large-scale applications.

[0037] Preferably, the molar ratio of the soluble alkali metal iodide to the soluble luminescent center ion halide is 3:(0.5-3), for example, it can be 3:0.5, 3:1, 3:1.5, 3:2, 3:2.5 or 3:3, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 3:(1.5-3).

[0038] Preferably, in the acid solution, the concentration of hydroiodic acid is 5-7 mol / L, for example, 5 mol / L, 5.5 mol / L, 6 mol / L, 6.5 mol / L or 7 mol / L; the concentration of hypophosphorous acid is 1-2 mol / L, for example, 1 mol / L, 1.2 mol / L, 1.4 mol / L, 1.6 mol / L, 1.8 mol / L or 2 mol / L, including but not limited to the listed values, and other values ​​not listed within the numerical range are also applicable.

[0039] In the present invention, the hydroiodic acid in the acid solution is used as a solvent to fully dissolve and mix the soluble alkali metal iodide and the soluble luminescent center ion halide, and the hypophosphorous acid is used as an inhibitor to inhibit the Cu + Oxidized to Cu 2+ .

[0040] Preferably, the preparation method further comprises cleaning and drying the yellow-green luminescent single crystal material obtained in step (3).

[0041] Preferably, the cleaning comprises cleaning with ethanol to remove residues.

[0042] Preferably, the drying temperature is 60°C-90°C, for example, 60°C, 65°C, 70°C, 75°C, 80°C, 85°C or 90°C, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable.

[0043] In a second aspect, the present application provides a yellow-green luminescent single crystal material, which is prepared by the preparation method described in the first aspect.

[0044] In the yellow-green luminescent single crystal material of the present invention, the luminescent center ions are evenly distributed in the alkali metal iodide lattice, and the doped luminescent center ions can form new luminescent centers in the alkali metal iodide lattice, giving it efficient luminescent properties in the yellow-green band. Compared with undoped alkali metal iodide materials, the introduction of luminescent center ions provides additional electronic states, which helps to improve the photoluminescent performance.

[0045] Preferably, the yellow-green luminescent single crystal material is a yellow-green luminescent Cu-doped KI single crystal material.

[0046] Preferably, in the high-efficiency yellow-green light-emitting Cu-doped KI single crystal material, the molar ratio of KI to CuI is 3:(0.5-3), for example, it can be 3:0.5, 3:1, 3:1.5, 3:2, 3:2.5 or 3:3, including but not limited to the listed values, and other unlisted values ​​within the numerical range are also applicable, preferably 3:(1.5-3).

[0047] In the yellow-green luminescent Cu-doped KI single crystal material of the present invention, Cu + Uniform distribution in the KI lattice, doped with Cu + It can form new luminescence centers in the KI lattice, giving it efficient luminescence characteristics in the yellow-green band.

[0048] In a third aspect, the present application provides a yellow-green light-emitting device, wherein the yellow-green light-emitting device comprises the yellow-green light-emitting single crystal material as described in the second aspect.

[0049] The yellow-green luminescent single crystal material of the present invention has significant luminescent properties in the yellow-green spectral region, meets the needs of solid-state lighting, optical sensors and display devices for high-efficiency luminescent materials, and has broad application prospects.

[0050] Compared with the prior art, the present invention has at least the following beneficial effects:

[0051] (1) The present invention adopts the solution cooling recrystallization method, a low-energy consumption and easy-to-control crystal growth process, to achieve the preparation of yellow-green luminescent single crystal materials at a relatively low temperature. Through the crystal growth process under specific temperature conditions, the luminescent center ions are ensured to be uniformly doped in the soluble alkali metal iodide lattice and the stable growth of the soluble iodide crystals is promoted, thereby improving the luminescence consistency and quantum yield of the yellow-green luminescent single crystal material. In addition, the temperature control of the solution cooling method is more precise and the operation is simple, the production efficiency is high, and it is suitable for large-scale production.

[0052] (2) The present invention achieves uniform distribution of luminescent center ions in soluble alkali metal iodide crystals. The doped luminescent center ions can form new luminescent centers in the alkali metal iodide crystal lattice, giving it efficient luminescence characteristics in the yellow-green band. It has efficient photoluminescence performance in the yellow-green band (approximately 450nm to 700nm), and the luminescence quantum yield is as high as 98.98%.

[0053] (3) The yellow-green luminescent single crystal material in the present invention has significant luminescence characteristics in the yellow-green spectral region, which meets the needs of solid-state lighting, optical sensors and display devices for high-efficiency luminescent materials and has broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0054] Figure 1 It is a process flow chart of the preparation method provided by the present invention.

[0055] Figure 2 It is a schematic diagram of the yellow-green luminescent single crystal material prepared in Example 5 of the present invention and the yellow-green light emitted.

[0056] Figure 3 It is the XRD spectrum of the yellow-green luminescent single crystal material prepared in Examples 1 to 6 and Comparative Example 1.

[0057] Figure 4 This is the TEM spectrum of the yellow-green luminescent single crystal material prepared in Example 5.

[0058] Figure 5 This is the EDS spectrum of the yellow-green luminescent single crystal material prepared in Example 5.

[0059] Figure 6 This is a diagram of the quantum yield of the yellow-green luminescent single crystal material prepared in Example 5.

[0060] Figure 7 This is the excitation spectrum of the yellow-green luminescent single crystal material prepared in Examples 1 to 6 and Comparative Example 1.

[0061] Figure 8 It is the emission spectrum of the yellow-green luminescent single crystal material prepared in Examples 1 to 6 and Comparative Example 1.

[0062] Fig. 9 This is the absorption spectrum of the yellow-green luminescent single crystal material prepared in Example 5 and Comparative Example 1.

[0063] Fig.10 It is the bandgap width spectrum of the yellow-green luminescent single crystal material prepared in Example 5 and Comparative Example 1. DETAILED DESCRIPTION

[0064] For the convenience of understanding the present invention, the present invention lists the following embodiments. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.

[0065] Example 1

[0066] This embodiment provides a yellow-green luminescent single crystal material, and the preparation method of the yellow-green luminescent single crystal material is as follows:

[0067] (1) mixing 0.3 mol of potassium iodide and 0.05 mol of copper iodide to obtain a mixture of potassium iodide and copper iodide;

[0068] (2) At a first dissolution temperature of 70°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 6.5 mol / L, and the concentration of hypophosphorous acid is 1.6 mol / L. Heat and stir for 3 hours to fully dissolve potassium iodide and copper iodide to obtain a first reactant solution, which is a saturated solution of potassium iodide. The first reactant solution is uniformly cooled from the first dissolution temperature of 70°C to a first end crystallization temperature of 20°C at a first cooling rate of 2°C / h, filtered to obtain first crystal grains, and the first crystal grains are washed with ethanol to remove residual reactant solution;

[0069] (3) At a second dissolution temperature of 70°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 6.5 mol / L, and the concentration of hypophosphorous acid is 1.6 mol / L. The mixture is heated and stirred for 3 hours to fully dissolve potassium iodide and copper iodide to obtain a second reactant solution, which is a saturated solution of potassium iodide. The first crystals obtained in step (2) are added to the second reactant solution, and the temperature is uniformly reduced from the second dissolution temperature of 70°C to the second end crystallization temperature of 20°C at a second cooling rate of 2°C / h. The obtained crystals are filtered, washed with ethanol, and dried at 60°C to obtain the yellow-green luminescent single crystal material.

[0070] Example 2

[0071] This embodiment provides a yellow-green luminescent single crystal material, and the preparation method of the yellow-green luminescent single crystal material is as follows:

[0072] (1) mixing 0.3 mol of potassium iodide and 0.1 mol of copper iodide to obtain a mixture of potassium iodide and copper iodide;

[0073] (2) At a first dissolution temperature of 50°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 6 mol / L, and the concentration of hypophosphorous acid is 1.5 mol / L. Heat and stir for 4 hours to fully dissolve potassium iodide and copper iodide to obtain a first reactant solution, which is a saturated solution of potassium iodide. The first reactant solution is uniformly cooled from a first dissolution temperature of 50°C to a first end crystallization temperature of 27°C at a first cooling rate of 0.71°C / h, filtered to obtain first crystal grains, and the first crystal grains are washed with ethanol to remove residual reactant solution;

[0074] (3) At a second dissolution temperature of 56°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 6 mol / L and the concentration of hypophosphorous acid is 1.5 mol / L. Heat and stir for 4 hours to fully dissolve potassium iodide and copper iodide to obtain a second reactant solution, which is a saturated solution of potassium iodide. The first crystals obtained in step (2) are added to the second reactant solution, and the temperature is uniformly reduced from the second dissolution temperature of 56°C to the second end crystallization temperature of 27°C at a second cooling rate of 0.71°C / h. The obtained crystals are filtered, washed with ethanol, and dried at 70°C to obtain a yellow-green luminescent single crystal material.

[0075] Example 3

[0076] This embodiment provides a yellow-green luminescent single crystal material, and the preparation method of the yellow-green luminescent single crystal material is as follows:

[0077] (1) mixing 0.3 mol of potassium iodide and 0.15 mol of copper iodide to obtain a mixture of potassium iodide and copper iodide;

[0078] (2) At a first dissolution temperature of 56°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 7 mol / L, and the concentration of hypophosphorous acid is 2 mol / L. Heat and stir for 4 hours to fully dissolve potassium iodide and copper iodide to obtain a first reactant solution, which is a saturated solution of potassium iodide. The first reactant solution is uniformly cooled from a first dissolution temperature of 56°C to a first end crystallization temperature of 24°C at a first cooling rate of 0.86°C / h, filtered to obtain first crystal grains, and the first crystal grains are washed with ethanol to remove residual reactant solution;

[0079] (3) At a second dissolution temperature of 56°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 7 mol / L and the concentration of hypophosphorous acid is 2 mol / L. Heat and stir for 4 hours to fully dissolve potassium iodide and copper iodide to obtain a second reactant solution, which is a saturated solution of potassium iodide. The first crystals obtained in step (2) are added to the second reactant solution, and the temperature is uniformly reduced from the second dissolution temperature of 56°C to the second end crystallization temperature of 24°C at a first cooling rate of 0.86°C / h. The obtained crystals are filtered, washed with ethanol, and dried at 60°C to obtain a yellow-green luminescent single crystal material.

[0080] Example 4

[0081] This embodiment provides a yellow-green luminescent single crystal material, and the preparation method of the yellow-green luminescent single crystal material is as follows:

[0082] (1) mixing 0.3 mol of potassium iodide and 0.2 mol of copper iodide to obtain a mixture of potassium iodide and copper iodide;

[0083] (2) At a first dissolution temperature of 65°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 6 mol / L and the concentration of hypophosphorous acid is 1 mol / L. Heat and stir for 6 hours to fully dissolve potassium iodide and copper iodide to obtain a first reactant solution, which is a saturated solution of potassium iodide. The first reactant solution is uniformly cooled from a first dissolution temperature of 65°C to a first end crystallization temperature of 26°C at a first cooling rate of 1.05°C / h, filtered to obtain first crystal grains, and the first crystal grains are washed with ethanol to remove residual reactant solution;

[0084] (3) At a second dissolution temperature of 63°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 6 mol / L and the concentration of hypophosphorous acid is 1 mol / L. The mixture is heated and stirred for 6 hours to fully dissolve potassium iodide and copper iodide to obtain a second reactant solution, which is a saturated solution of potassium iodide. The first crystals obtained in step (2) are added to the second reactant solution, and the temperature is uniformly reduced from the second dissolution temperature of 63°C to the second end crystallization temperature of 28°C at a first cooling rate of 1.08°C / h. The obtained crystals are filtered, washed with ethanol, and dried at 80°C to obtain a yellow-green luminescent single crystal material.

[0085] Example 5

[0086] This embodiment provides a yellow-green luminescent single crystal material, and the preparation method of the yellow-green luminescent single crystal material is as follows:

[0087] (1) mixing 0.3 mol of potassium iodide and 0.25 mol of copper iodide to obtain a mixture of potassium iodide and copper iodide;

[0088] (2) At a first dissolution temperature of 60°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 5 mol / L, and the concentration of hypophosphorous acid is 2 mol / L. Heat and stir for 5 hours to fully dissolve potassium iodide and copper iodide to obtain a first reactant solution, which is a saturated solution of potassium iodide. The first reactant solution is uniformly cooled from a first dissolution temperature of 60°C to a first end crystallization temperature of 25°C at a first cooling rate of 1.25°C / h, filtered to obtain first crystal grains, and the first crystal grains are washed with ethanol to remove residual reactant solution;

[0089] (3) At a second dissolution temperature of 60° C., a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 5 mol / L and the concentration of hypophosphorous acid is 2 mol / L. The mixture is heated and stirred for 5 h to fully dissolve potassium iodide and copper iodide to obtain a second reactant solution, which is a saturated solution of potassium iodide. The first crystals obtained in step (2) are added to the second reactant solution, and the temperature is uniformly reduced from the second dissolution temperature of 60° C. to the second end crystallization temperature of 25° C. at a first cooling rate of 1.25° C. / h. The obtained crystals are filtered, washed with ethanol, and dried at 60° C. to obtain a yellow-green luminescent single crystal material.

[0090] Example 6

[0091] This embodiment provides a yellow-green luminescent single crystal material, and the preparation method of the yellow-green luminescent single crystal material is as follows:

[0092] (1) mixing 0.3 mol of potassium iodide and 0.3 mol of copper iodide to obtain a mixture of potassium iodide and copper iodide;

[0093] (2) At a first dissolution temperature of 70°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 7 mol / L and the concentration of hypophosphorous acid is 1 mol / L. Heat and stir for 5 hours to fully dissolve potassium iodide and copper iodide to obtain a first reactant solution, which is a saturated solution of potassium iodide. The first reactant solution is uniformly cooled from a first dissolution temperature of 70°C to a first end crystallization temperature of 25°C at a first cooling rate of 1.84°C / h, filtered to obtain first crystal grains, and the first crystal grains are washed with ethanol to remove residual reactant solution;

[0094] (3) At a second dissolution temperature of 70°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 7 mol / L and the concentration of hypophosphorous acid is 1 mol / L. The mixture is heated and stirred for 5 hours to fully dissolve potassium iodide and copper iodide to obtain a second reactant solution, which is a saturated solution of potassium iodide. The first crystals obtained in step (2) are added to the second reactant solution, and the temperature is uniformly reduced from the second dissolution temperature of 70°C to the second end crystallization temperature of 25°C at a first cooling rate of 1.84°C / h. The obtained crystals are filtered, washed with ethanol, and dried at 90°C to obtain a yellow-green luminescent single crystal material.

[0095] Example 7

[0096] This embodiment provides a yellow-green luminescent single crystal material. The preparation method of the yellow-green luminescent single crystal material is the same as that of Embodiment 5, except that the first cooling rate in step (2) is 0.67°C / h and the second cooling rate in step (3) is 0.67°C / h.

[0097] Example 8

[0098] This embodiment provides a yellow-green luminescent single crystal material. The preparation method of the yellow-green luminescent single crystal material is the same as that of Embodiment 5, except that the first cooling rate in step (2) is 2.4°C / h and the second cooling rate in step (3) is 2.4°C / h.

[0099] Example 9

[0100] This embodiment provides a yellow-green luminescent single crystal material. The preparation method of the yellow-green luminescent single crystal material is the same as that of Embodiment 5 except that the copper iodide in step (1) is 0.0015 mol.

[0101] Example 10

[0102] This embodiment provides a yellow-green luminescent single crystal material. The preparation method of the yellow-green luminescent single crystal material is the same as that of Embodiment 5 except that the copper iodide in step (1) is 0.35 mol.

[0103] Comparative Example 1

[0104] This embodiment provides a KI single crystal material. The preparation method of the KI single crystal material is the same as that of Embodiment 5 except that copper iodide is not added in step (1).

[0105] Comparative Example 2

[0106] This embodiment provides a yellow-green luminescent material. The preparation method of the yellow-green luminescent material is the same as that of Embodiment 5, except that the cooling methods in step (2) and step (3) are both natural cooling.

[0107] Comparative Example 3

[0108] This embodiment provides a yellow-green luminescent single crystal material, and the preparation method of the yellow-green luminescent single crystal material is as follows:

[0109] (1) mixing 0.3 mol of potassium iodide and 0.25 mol of copper iodide to obtain a mixture of potassium iodide and copper iodide;

[0110] (2) At a first dissolution temperature of 60°C, a mixture of potassium iodide and copper iodide is added to an acid solution, wherein the concentration of hydroiodic acid in the acid solution is 6.5 mol / L, and the concentration of hypophosphorous acid is 1.6 mol / L. The mixture is heated and stirred for 5 hours to fully dissolve potassium iodide and copper iodide to obtain a first reactant solution, which is a saturated solution of potassium iodide. The first reactant solution is uniformly cooled from a first dissolution temperature of 60°C at a temperature rate of 1.25°C / h to a first end crystallization temperature of 25°C, and the cooling time lasts for 48 hours. The obtained crystals are filtered, washed with ethanol, and dried at 60°C to obtain a yellow-green luminescent single crystal material.

[0111] Performance Test:

[0112] The crystal structures of the yellow-green luminescent single crystal materials prepared in Examples 1-6 and Comparative Example 1 were tested by XRD.

[0113] The yellow-green luminescent Cu-doped potassium iodide single crystal material prepared in Example 5 was subjected to TEM test and EDS test.

[0114] The quantum dot yield, excitation peak, emission peak and bandgap width of the yellow-green luminescent single crystal materials prepared in Examples 1-10 and Comparative Example 1 were tested. The test results are shown in Table 1.

[0115] Table 1

[0116]

[0117] according to Figure 3 The XRD patterns shown in the figure show that the XRD diffraction peaks of the yellow-green luminescent single crystal materials prepared in Examples 1-6 all correspond to the PDF spectra of potassium iodide, proving that potassium iodide single crystal materials have been synthesized. At the same time, the peak position near 25.248° has different degrees of deviation, which is due to the Cu + The yellow-green luminescent single crystal material is successfully prepared by the solution cooling recrystallization method. Under ultraviolet light irradiation, the yellow-green luminescent single crystal material prepared by the present invention can emit yellow-green light.

[0118] Figure 4The diffraction fringe spacing of the single crystal material in the TEM spectrum shown is 0.357 nm, which corresponds to the (111) plane in the PDF of potassium iodide, indicating that the material is KI phase.

[0119] Figure 5 The EDS spectrum clearly shows that the potassium, copper and iodine elements in the material are evenly distributed, further proving that Cu + Successful doping.

[0120] From the data in Table 1, it can be found that in the yellow-green luminescent Cu-doped KI single crystal material prepared by the present invention, due to Cu + Uniform distribution in the KI lattice, doped with Cu + It can form new luminescent centers in the KI lattice, giving it efficient luminescence characteristics in the yellow-green band, and has efficient photoluminescence performance in the yellow-green band (about 560nm to 580nm), and the luminescence quantum yield can be as high as 98.98%. Compared with the undoped KI single crystal material in Comparative Example 1, Cu + The introduction of provides additional electronic states, giving the KI single crystal material yellow-green luminescence properties. Figure 7 and Figure 8 It can also be seen that the pure phase KI single crystal in Comparative Example 1 has almost no excitation peak and emission peak, that is, it has no excitation characteristics and photoluminescence characteristics, while the Cu + After doping, Examples 1 to 6 exhibited obvious excitation peaks at 349 nm and 361 nm, ie, they possessed excitation characteristics, and exhibited obvious emission peaks at the 561 nm yellow-green light band, ie, they possessed the characteristic of emitting yellow-green light.

[0121] According to the data of Comparative Example 2, natural cooling is adopted in both step (2) and step (3), and only powdered material can be obtained, but yellow-green luminescent single crystal material cannot be obtained. The luminescent performance in the yellow-green band is far worse than the yellow-green luminescent single crystal material prepared by uniform cooling at a certain cooling rate in the present invention. This is because natural cooling is not conducive to the growth of single crystals, and even single crystal materials cannot be grown.

[0122] By comparing the data of Example 5 with that of Comparative Example 3, if the yellow-green luminescent single crystal material is directly obtained by crystallization through step (2), instead of placing the first crystal grains in the reactant solution for the second crystallization according to the solution cooling recrystallization method of the present invention, it will be detrimental to the growth of the single crystal, and the size of the obtained single crystal will be too small, resulting in poor yellow-green luminescence performance.

[0123] By comparing the data of Example 5 with those of Example 7 and Example 8, it can be found that a cooling rate that is too large or too small is not conducive to the uniform distribution of the luminescent center ions in the alkali metal iodide lattice, nor is it conducive to the stable growth of alkali metal iodides, and the luminescence consistency and quantum dot yield of the yellow-green luminescent single crystal material are reduced.

[0124] By comparing the data of Example 5 with those of Example 9 and Example 10, it can be found that if the molar ratio of the luminescent center ions is too small, the number of luminescent centers will be insufficient, which leads to too low a quantum yield, while if the molar ratio of the luminescent center ions is too large, there will be too many defects in the crystal and the lattice distortion will be too large, thus affecting the luminescence efficiency of the yellow-green luminescent single crystal material. Therefore, if the molar ratio of the luminescent center ions is too small or too large, the photoluminescence performance of the prepared yellow-green luminescent single crystal material will deteriorate and the quantum yield will be too low, thereby affecting its high-efficiency luminescence characteristics in the yellow-green band.

[0125] The applicant declares that the present invention illustrates the detailed method of the present invention through the above-mentioned embodiments, but the present invention is not limited to the above-mentioned detailed method, that is, it does not mean that the present invention must rely on the above-mentioned detailed method to be implemented. Those skilled in the art should understand that any improvement of the present invention, equivalent replacement of various raw materials of the product of the present invention, addition of auxiliary components, selection of specific methods, etc., all fall within the protection scope and disclosure scope of the present invention.

Claims

1. A method for preparing a yellow-green luminescent single crystal material, characterized in that: The preparation method comprises: (1) mixing a soluble alkali metal iodide and a soluble luminescent center ion halide to obtain a mixture; (2) dissolving the mixture of step (1) in an acid solution at a first dissolution temperature to obtain a first reactant solution, and cooling the first reactant solution from the first dissolution temperature to a first end crystallization temperature at a first cooling rate to obtain first crystals; (3) dissolving the mixture of step (1) in an acid solution at a second dissolution temperature to obtain a second reactant solution, adding the first crystal grains of step (2) to the second reactant solution, and cooling from the second dissolution temperature to a second end crystallization temperature at a second cooling rate to obtain the yellow-green light-emitting single crystal material; The first reactant solution and the second reactant solution are both saturated solutions of soluble alkali metal iodides; The acid solution includes a combination of hydroiodic acid and hypophosphorous acid.

2. The preparation method according to claim 1, characterized in that: Step (2) the first dissolution temperature is 50°C-70°C; Preferably, the first end crystallization temperature in step (2) is 20°C-30°C; Preferably, the second dissolution temperature in step (3) is 50°C-70°C; Preferably, the second end crystallization temperature in step (3) is 20°C-30°C; Preferably, the first dissolution temperature is the same as the second dissolution temperature; Preferably, the first end crystallization temperature is the same as the second end crystallization temperature.

3. The preparation method according to claim 1 or 2, characterized in that: Step (2) the first cooling rate is 0.7°C / h-2°C / h, preferably 1°C / h-1.6°C / h; Preferably, in step (3), the second cooling rate is 0.7°C / h-2°C / h, preferably 1°C / h-1.6°C / h; Preferably, the first cooling rate is the same as the second cooling rate.

4. The preparation method according to any one of claims 1 to 3, characterized in that The soluble alkali metal iodide includes potassium iodide; Preferably, the soluble luminescent central ion halide comprises copper iodide.

5. The preparation method according to any one of claims 1 to 4, characterized in that: The molar ratio of the soluble alkali metal iodide to the soluble luminescent center ion halide in the reactant solution is 3:(0.5-3), preferably 3:(1.5-3).

6. The preparation method according to any one of claims 1 to 5, characterized in that: In the acid solution, the concentration of hydroiodic acid is 5-7 mol / L, and the concentration of hypophosphorous acid is 1-2 mol / L.

7. The preparation method according to any one of claims 1 to 6, characterized in that: The preparation method further comprises cleaning and drying the yellow-green luminescent single crystal material obtained in step (3); Preferably, the cleaning comprises cleaning with ethanol to remove residues; Preferably, the drying temperature is 60°C-90°C.

8. A yellow-green luminescent single crystal material, characterized in that: The yellow-green luminescent single crystal material is prepared by the preparation method according to any one of claims 1 to 7.

9. The yellow-green luminescent single crystal material according to claim 8, characterized in that: The yellow-green luminescent single crystal material is a yellow-green luminescent Cu-doped KI single crystal material; Preferably, in the yellow-green luminescent Cu-doped KI single crystal material, the molar ratio of KI to CuI is 3:(0.5-3), preferably 3:(1.5-3).

10. A yellow-green light emitting device, characterized in that: The yellow-green light-emitting device comprises the yellow-green light-emitting single crystal material as claimed in claim 8 or 9.

Citation Information

Patent Citations

  • High-fluorescence-efficiency inorganic lead-free perovskite material and preparation method thereof

    CN112480911A

  • Cuprous iodide crystal growing method

    CN101928984A

  • Crystal growth promoter and method of producing metallic chalcogenide compound using the same

    JP2015193513A

  • Organic-inorganic hybrid material and perovskite solar cell using same

    US20200294727A1